Control of the linear interval systems using fuzzy logic and principle of separation of the models. - Lân, Vũ Như; Hưng, Vũ Chấn; Phu, Đặng Thành; Nam, Bạch Đông (Journal of Computer Science and Cybernetics, 2012)
-